A systematic review on risk assessment tools for identifying individuals at risk of developing prediabetes and Type 2 Diabetes - Nazri, Amirah Farhana; Soe, May Khin Soe; Ashara, Nurul Nadiah (CR Subscription Agency, 2023)
Introduction: Type 2 diabetes mellitus (T2DM) is a common metabolic disease that leads to various complications and financial distress. T2DM is influenced by a complex interplay of genetic, metabolic, and environmental risk factors. Moreover, the rapid increase of prediabetes and type 2 diabetes world-wide have the effect of gaining attention to predict it since early age. However, early detection and appropriate treatments can successfully prevent or delay the development of T2DM and its complication. Thus, identifying high risk persons should be done using self-assessment questionnaires, tools and scoring method. It is crucial to choose the right diabetes risk assessment tools in places with diverse populations. Objectives: To systematically review all recent research on the risk assessment tool used for identifying people at risk of developing T2DM. Methods: A comprehensive systematic literature review was performed using multiple electronic databases like PubMed, Scopus, and ScienceDirect. Selection criteria included adult aged 18 years and older and taking diabetes risk assessments. Data from included studies were extracted using a predesigned data extraction tool. Joanna Briggs Institute Critical Appraisal checklists were used as the main tool for critical appraisal. Results: Fifteen published studies between 2012 to 2022 were finally included out of 271 articles obtained from databases. Some had been removed due to incomplete criteria. Nine of the included studies use one risk assessment tools and six of them uses multiple tools. The included diabetes risk assessment tools are FINDRISC, IDRS, RAPID, QDiabetes score, ADA, QDRS and CANRISK. Conclusion: The chance of developing prediabetes and T2DM and is increased by a variety of modifiable risk factors. It is possible to identify individuals with high-risk group by using a simple, practical, non-invasive and affordable diabetes risk score.